Measurement of Antecedent Factors of E-Commerce Shopee Purchase Decisions for Creative Industry Consumers - Murtianingsih, Murtianingsih -; Fitriani, Yuniar (Fakultas Ekonomi, UIN Maliki Malang, 2024)
Online shopping behavior has become a trend in society today, the development of information technology has given rise to various e-commerce platforms. Shopee is one of the best E-Commerce in the Appstore and Playstore, providing opportunities for business actors to improve their business and expand market reach. In line with the Go-Digital program, creative industry entrepreneurs, especially crafts and fashion, have the opportunity to grow by utilizing stores on Shopee. This research is to examine the antecedents’ factors of purchasing decision factors which include price, product variety, advertising who have made transactions purchasing craft and fashion products from several stores at the E-Commerce Shoppe. The sample used was 100 respondents and complete data was obtained in accordance with research needs 96. The questionnaire distributed used a Linkert scale. This research uses an explanatory research method with a multiple linear regression, the indicators for each variable have fulfilled the elements of validity and reliability with a Cronbach Alpha more than 0,600 and the research results show that price, product variety and advertising have a significant positive effect on buying decision. Consumers on the Shopee e-commerce consider these three factors when deciding to purchase creative industry products.